Can Malawi's poor afford free tuberculosis services? Patient and household costs associated with a tuberculosis diagnosis in Lilongwe - Julia R Kemp; Gillian Mann; Bertha Nhlema Simwaka; Felix ML Salaniponi; Stephen Bertel Squire
OBJECTIVE: To assess the relative costs of accessing a TB diagnosis for the poor and for women in urban Lilongwe, Malawi, a setting where public health services are accessible within 6 kilometres and provided free of charge. METHODS: Patient and household direct and opportunity costs were assessed from a survey of 179 TB patients, systematically sampled from all public and mission health facilities in Lilongwe. Poverty status was determined from the 1998 Malawi Integrated Household Survey (MIHS). FINDINGS: On average, patients spent US$ 13 (MK 996 or 18 days' income) and lost 22 days from work while accessing a TB diagnosis. For non-poor patients, the total costs amounted to 129% of total monthly income, or 184% after food expenditures. For the poor, this cost rose to 248% of monthly income or 574% after food. When a woman or when the poor are sick, the opportunity costs faced by their households are greater. CONCLUSION: Patient and household costs of TB diagnosis are prohibitively high even where services are provided free of charge. In scaling up TB services to reach the Millennium Development Goals, there is an urgent need to identify strategies for diagnosing TB that are cost-effective for the poor and their households.